2019
DOI: 10.1017/s0959270919000248
|View full text |Cite
|
Sign up to set email alerts
|

The world’s largest breeding colony of Leach’s Storm-petrel Hydrobates leucorhous has declined

Abstract: SummaryDespite the global significance of the Leach’s Storm-petrel Hydrobates leucorhous colony on Baccalieu Island, Newfoundland and Labrador, Canada, the estimate of 3.36 million breeding pairs reported for 1984 by Sklepkovych and Montevecchi stands as the single published population estimate for the world’s largest colony. This study increases knowledge of this population by analysing data from additional independent surveys conducted in 1984 and 1985, and by updating the population status with a survey con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 16 publications
(20 reference statements)
3
25
1
Order By: Relevance
“…Despite the decline in the north, the highest occupied burrow densities (0.091 ± 0.02 burrows/m²) on the island were observed in the open habitat (fern, grass, shrub/bramble) of the north. This shift in preference of habitat from forest to open found in our study contrasts with other research showing that storm-petrels nest at greater densities in forested habitat as compared to open habitat , Robertson et al 2006, Wilhelm et al 2015, although recent census work on Baccalieu Island has shown dramatic declines in the number of storm-petrels nesting in forest as well (Wilhelm et al 2019). As burrow densities are directly correlated to the suitability of habitat for storm-petrel nesting (Robertson et al 2006), these results suggest that changes in suitable habitat may have occurred.…”
Section: Influence Of Habitat On Nest Site Usecontrasting
confidence: 99%
See 3 more Smart Citations
“…Despite the decline in the north, the highest occupied burrow densities (0.091 ± 0.02 burrows/m²) on the island were observed in the open habitat (fern, grass, shrub/bramble) of the north. This shift in preference of habitat from forest to open found in our study contrasts with other research showing that storm-petrels nest at greater densities in forested habitat as compared to open habitat , Robertson et al 2006, Wilhelm et al 2015, although recent census work on Baccalieu Island has shown dramatic declines in the number of storm-petrels nesting in forest as well (Wilhelm et al 2019). As burrow densities are directly correlated to the suitability of habitat for storm-petrel nesting (Robertson et al 2006), these results suggest that changes in suitable habitat may have occurred.…”
Section: Influence Of Habitat On Nest Site Usecontrasting
confidence: 99%
“…The annual rate of decline observed in the predominantly forested northern region aligns closely with annual rates of change observed in open habitat in a major Newfoundland colony Montevecchi 1999, Wilhelm et al 2015). Moreover, declines observed over the past ~30 years at the largest colony for this species (Baccalieu Island, Newfoundland and Labrador) show annual rates of decline of 1.4% per year and the largest declines were observed in forested habitats (Wilhelm et al 2019), similar to our results on Kent Island. Given these similar declines among multiple colonies and the very high nest-site fidelity observed with this species (Pollet et al 2019), dispersal is an unlikely mechanism for the decreasing population on Kent Island.…”
Section: Breeding Population Status and Trendsupporting
confidence: 89%
See 2 more Smart Citations
“…We also acknowledge that the distributions of occupied burrow densities within habitats tend to show a right skew, and therefore the Delta method may not fully capture the true shape of the underlying distributions. In general, we followed the approach in Wilhelm et al (68), in which the number of occupied burrows in each plot is estimated from the data, and randomization procedures are used to propagate uncertainty through to the final estimates of colony size. We only reestimated surveys from 2004, 2008, and 2011 because there was sufficient data for a meaningful population estimate.…”
mentioning
confidence: 99%